PENGAJARAN BAHASA INGGRIS BERBASIS VIDEO ANIMASI PADA SISWA KELAS V PENDIDIKAN DASAR - Fauzi, Ali (PREMIERE : Journal of Islamic Elementary Education, 2024)
Abstract English is an international language used by most people in the world, so being able to speak English is a mandatory skill. Responding to this urgency, the Indonesian government has set a policy so that English is taught since Elementary School as local content. Learning English at the elementary school level is considered difficult and demands teacher competence and requires innovative strategies, methods, and media. Interesting media such as animated videos are still quite rarely used in elementary schools, especially in rural areas. SDN Sendanghaji is one of the schools that tries to apply this method despite the limited facilities owned by the school. In this case, this study aims to describe how teachers teach, what approaches, strategies, methods and media they use during the teaching and learning process. This research is a qualitative research in the form of a case study. The approach in this study is a phenomenological approach where researchers observe phenomena and facts during English learning and then describe them. The data in this study are in the form of lesson plans and facts that occur in the classroom and data sources are taken from facts and phenomena in the classroom and from the books used. The results of the study indicate that teachers have taught students well and successfully. Teachers use lecture, Q&A or discussion methods and role-playing; teachers apply scientific approaches and learning models to explore potential; teachers use animated video media supported by textbooks such as Student's Book My Next Words, Smart English Book and Grow with English; teachers use supporting equipment such as LCD Projectors and others, and are able to manage classes and learning time well. Students are enthusiastic about following lessons; they are motivated to practice and do homework and are able to understand the lessons very well.